Analisis faktor-faktor yang mempengaruhi kinerja keuangan Bank Umum Syariah - Kurniawan, Heri (Nur Science Institute, 2022)
This study aims to examine how much Intellectual Capital, Islamic Corporate Governance, Islamic Social Responsibility, Islamic Ethical Identity, and Zakat can affect Islamic commercial banks' financial performance. The population in this study is Islamic Commercial Banks in Indonesia. The method of determining the sample using the purposive sampling method. The data used is secondary data. Hypothesis testing is done by using multiple regression analysis techniques. The study results indicate that Intellectual Capital and Islamic Ethical Identity affect financial performance. Islamic Corporate Governance does not affect Financial Performance, Islamic Social Responsibility, Islamic Corporate Governance, Islamic Social Responsibility, and Zakat does not affect Financial Performance of Islamic Commercial Banks. Simultaneously, these independent variables have a positive and significant influence on the Financial Performance of Islamic Commercial Banks.